DESKRIPSI KEMAMPUAN MULTIREPRESENTASI DALAM MENYELESAIKAN SOAL PADA MATERI HUKUM NEWTON DI SMAN 1 SUNGAI RAYA - Nabila, Putri; Sirait, Judyanto; Habellia, ray Cinthya (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Solving problems on Newton's law material is not enough just to memorize the formula, students must have the ability to use multiple representations because the concept of Newton's law is very complex, students must be able to analyze the forces acting on blocks according to the idea to make it easier to solve problems. This research aims to describe students' abilities and answer patterns in solving Newton's law of force on an inclined plane using multiple representations. This research used qualitative methods involving 34 students in class XI MIPA SMA Negeri 1 Sungai Raya for the 2023/2024 academic year. Data collection was carried out by giving multi-representation tests in the form of description tests and interviews. From the results of multi-representation tests and interviews, it was found that almost all students were able to write style names completely, and a few errors were found in writing style names. In describing force diagrams, it was found that all students could describe normal force and gravity force, but it was found that some students could not describe pushing force, friction force, and rope tension force. Then, the ability of students to solve mathematical equations, overall very few students can solve mathematical equations completely and precisely.